Intragenic Copy Number Variation in the Filaggrin Gene in Ethiopian Patients with Atopic Dermatitis. Issue 3 (10th March 2017) - Fernandez, Kerstin; Asad, Samina; Taylan, Fulya; Wahlgren, Carl‐Fredrik; Bilcha, Kassahun D.; Nordenskjöld, Magnus; Winge, Mårten C.G.; Bradley, Maria
Abstract: Genetic variants in filaggrin ( FLG ) involving truncating mutations or intragenic copy number variation are strongly associated with the risk of developing atopic dermatitis (AD) in European and Asian populations. Few loss‐of‐function mutations have been identified in Africans, although an association between FLG copy number variation and AD severity in a small African American cohort has been proposed. We studied the association between FLG copy number and AD in 132 Ethiopians and found no association between AD severity and FLG copy number, suggesting that other, still unidentified genetic factors are of more importance in predisposing Ethiopians to AD.